TAM vs. PCI: An Analysis on the Theoretical Model Parsimony and Robustness across Cultures - Yew-Siang, Poong; Uehenna Cyril, Eze (2008)
This paper aims to evaluate the suitability of two classic models of technology acceptance applied in studying e-commerce adoption in Malaysia. Compared with Western countries. Malaysia is a multi racial and multi cultural society. Since established model of technology acceptance evolved from Western countries, there is a need to choose the appropriate theoretical model that is able to predict Malaysian e-commerce acceptance. This paper presents a comparison between Technology Acceptance Model and Perceived Characteristics of Innovation from the perspective of model parsimony and robustness across cultures.